1986
DOI: 10.1111/j.1432-1033.1986.tb10474.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the phosphoglycerate kinase gene of Saccharomyces cerevisiae increases when fermentative cultures are stressed by heat‐shock

Abstract: The single gene for phosphoglycerate kinase (PGK) in the haploid genome of Saccharomyces cerevisiae is expressed to a very high level in cultures fermenting glucose. Despite this it responds to heat-shock, When S . cerevisiae growing exponentially on glucose media was shifted from 25 "C to 38 "C transient increases of 6 -7-fold in cellular PGK mRNA were observed. This elevation in PGK mRNA still occurred in the presence of the protein-synthesis inhibitor cycloheximide, but was not observed in cells bearing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 39 publications
(17 reference statements)
2
26
0
1
Order By: Relevance
“…3 b). The temperature of 42 "C is about 3 "C above the maximum for growth, and close to the maximum temperature at which S. cerevisiae will still display synthesis of HSPs (Piper et al, 1986. Normally, after cells are shifted to 42 "C, an initial 'burst' of HSP synthesis is followed by a progressive cessation of all protein synthesis over about 1 h. This is apparent from the labelling of S. cerevisiae ~1278b in Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…3 b). The temperature of 42 "C is about 3 "C above the maximum for growth, and close to the maximum temperature at which S. cerevisiae will still display synthesis of HSPs (Piper et al, 1986. Normally, after cells are shifted to 42 "C, an initial 'burst' of HSP synthesis is followed by a progressive cessation of all protein synthesis over about 1 h. This is apparent from the labelling of S. cerevisiae ~1278b in Fig.…”
Section: Resultsmentioning
confidence: 74%
“…pombe cells actively growing at 25 "C are shifted to 48 "C there is rapid protein synthesis arrest; no HSPs are synthesized and these cells, uninduced for thermotolerance, quickly die. Pulselabelling studies have shown that neither yeast can synthesize HPSs above 42-43 "C (Piper et al, 1986; also unpublished observations). At 48 "C pmal .l conferred higher thermotolerance (Figs 1 a and 2a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fba1p, which encodes fructose-1,6-biphosphate aldolase was required for glycolysis and gluconeogenesis and located in mitochondrial outer membrane surface upon oxidative stress (Rinnerthaler et al, 2006). Pgk1p was abundantly expressed in cells grown in glucose, and transcription was increased by heat shock (Piper et al, 1986) and regulated by the transcription factors Rab1p, Abf1p, and Reb1p (Packham et al, 1996). In particular, enolase and Ssb protein are major targets of protein damage in WT yeast cells exposed to oxidative stress (Cabiscol et al, 2000;Reverter-Branchat et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…4). Piper et al (18) concluded that the role of PGK may be to assist cells repressed in mitochondrial function during recovery following heat shock. In our experiments, the observation that PGK promoter stimulation was observed only at midlog phase in cells cultured in PQ-containing medium, and not after a 1 h exposure to the oxidant, further supports the notion that PGK is especially required in the recovery stage.…”
Section: Discussionmentioning
confidence: 99%